2018
DOI: 10.17650/2222-8721-2018-8-2-42-52
|View full text |Cite
|
Sign up to set email alerts
|

Early epileptic encephalopathy associated with SCN2A mutations: clinical and genetic description of eight novel patients

Abstract: Описано большое количество моногенных заболеваний, в клинической картине которых наблюдаются судороги. Среди них особое место занимают ранние эпилептические энцефалопатии (РЭЭ)-генетически гетерогенная группа заболеваний, характеризующихся манифестацией судорог до 2-летнего возраста и тяжелым прогрессирующим течением. К настоящему времени идентифицированы 58 генетических вариантов РЭЭ. Цель исследования-анализ частоты встречаемости и клинико-генетических характеристик РЭЭ II типа в выборке больных из популяции… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In the described population, mutations in the SCN1A gene were most frequently detected, and were in 15 patients, which is consistent with all world and other Russian data. 8,10,11,12 On the second place are the mutations in the CDKL5, PCDH19 genes, which were detected in 5 patients each, MECP2, SMC1A, UBEZA were in 4 patients each and GABRA1 were in 3 patients. Other Russian data showed that with epileptic encephalopathies, the second most detectable were mutations in the genes MECP2, responsible for the development of Rett syndrome, and TPP1, responsible for the development of neuronal ceroid lipofuscinosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the described population, mutations in the SCN1A gene were most frequently detected, and were in 15 patients, which is consistent with all world and other Russian data. 8,10,11,12 On the second place are the mutations in the CDKL5, PCDH19 genes, which were detected in 5 patients each, MECP2, SMC1A, UBEZA were in 4 patients each and GABRA1 were in 3 patients. Other Russian data showed that with epileptic encephalopathies, the second most detectable were mutations in the genes MECP2, responsible for the development of Rett syndrome, and TPP1, responsible for the development of neuronal ceroid lipofuscinosis.…”
Section: Discussionmentioning
confidence: 99%